Salinidade, luz e sacarose na micropropagação de mandioca - Cardoso, Milena Nascimento (2016)
Cassava (Manihot esculenta Crantz) belongs to the family Euphorbiceae, Manihot genus, which consists of 98 species Manihot esculenta being the only commercially produced. It is usually propagated vegetatively, but several factors such as the process of soil salination can cause serious damage to crops, decreasing the production of cassava. For the maintenance of physiological processes in adverse conditions such as salt stress, plants accumulate amino acids compatible to the cytosol, such as proline, which assists in maintaining the osmotic pressure, keeping the water absorption. micropropagation in vitro seedlings require a number of requirements, such as growth room with artificial light and carbon source, which together with the low survival rate in the acclimatization, more expensive the final product. The use of natural light even in vitro rooting phase, called photoautotrophy, and the decrease in sucrose concentration appears as potential possibilities to improve the acclimatization of plants, helping reduce costs and enabling trade. In Chapter 1, six genotypes were used in the ex vitro salinity experiment: Sergipe, Lagoão, BRS Verdinha, BRSTapioqueira, BRS Kiriris and BRS Formosa. During acclimatization, the seedlings were watered weekly with MS liquid solution, with or without added 4 or 8 g.L-1 NaCl, making three treatments. After 90 days it was found that the cultivars BRS Formosa and BRS Kiriris had higher salt tolerance and proline accumulation was intensified in all varieties from the addition of salt to the substrate. In Chapter 2, the treatments were applied in vitro rooting phase, and with different concentrations of sucrose (10, 20, 30 and 40 g.L-1) for Tapioqueira and Lagoão for 45 days and transferred to the greenhouse. After 60 days were assessed: root number, leaf number, number of tubercle, shoot length, root length, number of buds, shoot dry weight, root dry weight and survival rate. The two genotypes developed better at higher sucrose concentrations. In a second experiment, the treatments sucrose (10, 20 and 30 g.L-1) and light (natural and artificial growth area) were applied at the same stage, and the BRS Formosa, BRS Verdinha and Lagoão. After 45 days under natural light or artificial light, the explants were transferred to the greenhouse. After 60 days, the BRS Formosa and Lagoão performed better under natural light and high sucrose concentrations, as BRS Verdinha had better development under natural light, but with lower carbohydrate concentration. In Chapter 3, explants of Lagoão, BRS Tapioqueira and BRS Verdinha were inoculated in MS medium without growth regulators and with different salt concentrations (0, 25, 50, 75 and 100 mM). After 90 days, BRS Verdinha and BRS Tapioqueira had higher salt tolerance and BRS Tapioqueira showed greater potential to osmoregulation due to its high proline production.